The IMPLEMENTASI MODEL CPS DENGAN METODE MIND MAPPING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN HASIL BELAJAR SISWA AKUNTANSI - Marshanda Cristina Sari Malau; Choms Gary Ganda Tua Sibarani; Sondang Aida Silalahi; Rini Herliani (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
Problem-solving abilities and student learning outcomes are essential things to pay attention to in learning. This research aims to describe the effectiveness of applying the Creative Problem-Solving model assisted by the mind mapping method in improving problem-solving abilities and learning outcomes in tax administration subjects with the subject matter of Corporate Income Tax payable. The research was carried out using the classroom action research method in two cycles. Each cycle consists of two meetings, divided into four stages: planning, action, observation, and reflection. The subjects of this research were students of XI AKL 2 SMK Negeri 1 Pematangsiantar, totalling 33 students. The data collection techniques used in this research are observation and tests. The percentage of the average value of problem-solving ability in cycle I was 60.60% and increased in cycle II to 88.75%. Meanwhile, for student learning outcomes in cycle I, the percentage of classical completion was 48.4%; in cycle II, it increased to 100%. So, the Creative Problem-Solving model assisted by the Mind Mapping method can improve problem-solving abilities and student learning outcomes.